ANALISIS PENGARUH KUALITAS LAYANAN DAN KEPUASAN KONSUMEN TERHADAP MINAT KUNJUNG PADA OBYEK WISATA PANTAI WIDURI DI PEMALANG - Yunantias, Willi; Kusumawardhani, Amie (Diponegoro Journal of Management, 2015)
The establishment of interesting attractions is one way that can be done to increase the number of visitors or tourists with attention to the quality of the services provided such as building, cleaning, and security. This research was conducted that analyze whether service quality and customer satisfaction have an influence on visit intention the tourists go to the Widuri beach.In this study, the sample size used was 143 respondents. Respondents used is that ever visited the Widuri beach more than once. Data analysis using SEM (Structural Equation Modeling). The analysis results the environment and services have significant and positive effect on customer satisfaction, accessibility have negative effect on customer satisfaction, and customer satisfaction have significant and positive effect on the visit intention.